RANCANG BANGUN KLINOSTAT 2-D DENGAN PEROTASI MOTOR DC D06D401E - Oka Guna Antara, I Made; Supardi, I Wayan; Rupiasih, Ni Nyoman (BULETIN FISIKA; Vol 17 No 2 (2016): BULETIN FISIKA, 2016)
It has successfully developed a 2-D clinostat using a DC motor rotation D06D401E. The tool has angular velocity (?') of 1.67 to 93.53 rpm with changes intervals of 1.67 rpm. The reading of angular velocity is performed by DI-REV#1 module, the reading of data by the ATmega16 microcontroller on timer/counter T1 PortB.1 and 2x16 LCD as a data display. The accuracy of the angular velocity which compared by a digital tachometer DT-2234C + (?' ref ) is 99.91%. The input voltage to a DC motor supplied by a variable power supply with range of 0-5 VDC, with the linearity between power and angular velocity of 99.13%. At the smallest value of the angular speed of 1.67 rpm obtained a Relative Centrifugal Force (RCF) of 4.68 ´ 10 -5 g.